Cost Effectiveness Analysis of Crystalloid and Crystaloid-Colloid Combination on Dengue Fever without Shok in Bhakti Asih General Hospital Tangerang - Suratni Suratni; Yusi Anggriani; Agusdini Banun (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Dengue fever is an infectious disease caused by virus transmitted through Aedes aegypty. The high incidence dengue fever can lead to increased healthcare costs. This study was conducted to analyze the effectiveness and direct cost of medical patients dengue fever without shock use fluid therapy by comparing crystalloid and crystalloid colloid combination. The subjects were 171 patients divided into two groups: 106 patients with crystalloid and 65 patients with crystalloid colloid combination. Assessed of effectiveness treatment and the mean medical costs. The results showed reviewed from hematocrit value no difference (p>0.05) in both study groups. The mean total cost of treatment for crystalloid Rp 4.005.223, the crystalloid colloid combination Rp 5.525.407. The highest cost of drug costs was 31.75% of the total cost crystalloid, 40.9% of the total cost crystalloid colloid combination. There was a significant difference between mean cost and two study groups (p0.05) with effectiveness treatment. Conclusion crystalloid have the same effectiveness as crystalloid colloid combination fluids at lower costs.